Plasmodium Falciparum Versus Plasmodium Vivax: Which Is a Lesser Evil? - Rathod , Chirag C; Deshpande , Shubhangi V; Rana , Himanshu M; Godbole , Varsha Y; Patel , Amul; Patel , Vaibhav; Darad , Dimple; Panchal , Maulik (National Journal of Community Medicine, 2012)
Background: With changing spectrum, different grades of biochemical & haematological changes generally found to be more severe with p. falciparum, now frequently seen with p. vivax. Present study intends to find species specific differences in diseases progression & complications. Methodology: A retrospective study of Malaria-patients admitted at GMERS Medical College & Hospital, Vadodara from january-2011to december-2011 was done. p. falciparum, P. Vivax were diagnosed by demonstrating asexual forms of parasites in peripheral blood smear, haematological & biochemical tests were analyzed. Results: Out of 1093 cases, 781 were slide positive, remaining 312 were treated on clinical-ground .Of 781 cases, 443 (56%) p. falciparum, 327 (42%) P. Vivax and 11(2%) were mixed Infection. Male to female ratio was 1.8:1&0.8:1 in p. falciparum & P. vivax, respectively. Fever, Prodroms, GI symptoms, Liver -dysfunction (51%vs47%), Renal- dysfunction (52%vs48%) were equally frequent; whereas Hemolysis, Bleeding tendency, Breathlessness and altered sensorium were more in p. falciparum. Anemia (56%), Thrombocytopenia (60%), Pancytopenia (54%), Hemolysis (65%) was more frequent in p. falciparum. Leucopenia (54%) was more frequent in p. Vivax. Conclusion: In contrast to earlier studies, which have proven p. falciparum to be more fatal & complicated, it was noted in present study that P. Vivax species was frequent cause of overall slide-positive cases causing complications head to head with p. falciparum. Anemia, Hepato-renal dysfunctions were equally frequent, nonfatal leucopenia more in p. Vivax, while hemolysis and thrombocytopenia was more in p. falciparum. If ignored complications can alter clinical course & be equally fatal in p. vivax malaria. Hence p. vivax can no more be considered as benign infection and can be equally lethal.